2015
DOI: 10.1590/1983-1447.2015.02.48427
|View full text |Cite
|
Sign up to set email alerts
|

Records of growth and development data in the child health handbook

Abstract: The low rate of growth and development data input in the handbooks reveals the need to create awareness among the population, health care professionals and managers on the importance of handbooks, and the need to invest in training and the empowerment of professionals in relation to its proper use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
10

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 10 publications
1
23
0
10
Order By: Relevance
“…Usage percentages were lower in comparison to those in previous studies conducted in Japan (Hokama T et al, 2000;Takeda M et al, 2001;Fujimoto S et al, 2001;Aoki M et al, 2009). However when comparing the results of studies in Brazil (Abud SM et al, 2015;Palombo CN et al, 2014) our results are higher as only 9% of those studies Child healthcare handbook (CHH) contained growth charts. In our survey of the usage of the Maternal and Child Health Handbook by mothers whose children had the 1-year-6-month infant health examination, most mothers reported that in the Maternal and Child Health Handbook, the most helpful record for them was the "immunization record" but they felt that the growth charts were not helpful although they kept records in it (Fujimoto et al, 2001).…”
Section: Resultsmentioning
confidence: 58%
“…Usage percentages were lower in comparison to those in previous studies conducted in Japan (Hokama T et al, 2000;Takeda M et al, 2001;Fujimoto S et al, 2001;Aoki M et al, 2009). However when comparing the results of studies in Brazil (Abud SM et al, 2015;Palombo CN et al, 2014) our results are higher as only 9% of those studies Child healthcare handbook (CHH) contained growth charts. In our survey of the usage of the Maternal and Child Health Handbook by mothers whose children had the 1-year-6-month infant health examination, most mothers reported that in the Maternal and Child Health Handbook, the most helpful record for them was the "immunization record" but they felt that the growth charts were not helpful although they kept records in it (Fujimoto et al, 2001).…”
Section: Resultsmentioning
confidence: 58%
“…Another aspect revealed by professionals, such as the difficulty in growth follow-up that referred to the lack of CHB, although, the filling in and the usage of this instrument do not take place adequately, especially related to growth and development charts (11) . Additionally, based on the perception of professionals, mothers do not use the CHB and do not value them, the same way the professionals themselves do, as that contributes to following up child growth that does not occur as recommended, thereby hindering the early detection of easily avoidable problems.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of being considered as low-cost procedures and easily achievable in healthcare services, studies have shown diverse problems in putting such practices into effect, such as the scarcity of knowledge, and the unpreparedness of healthcare professionals to deal with maternal breastfeeding (9) and feeding children under one year old (10) , infrequent records in the Child Health Booklet (11) , difficulties in performing and interpreting growth curves (12) , as well as service infrastructure problems, as the minimum equipment, such as scales and anthropometers are unavailable for following up growth (13) .…”
Section: Introductionmentioning
confidence: 99%
“…Atualmente, está em construção um modelo assistencial em que a criança deixa de ser compreendida como ser unicamente biológico, que privilegia cuidado assistencial centrado em suas especificidades e de sua família, mediante a construção de redes de apoio, buscando sua integralidade (11) . Nesta nova perspectiva, o cuidado de enfermagem deve promover e restaurar o bem-estar físico, psíquico e social, considerando aspectos intrínsecos ligados à sua condição de criança e reconhecendo o protagonismo familiar, bem como as legislações que garantem suas especificidades (12)(13) .…”
Section: Discussionunclassified